Membrane for hydrogen production, alkaline water electrolysis component using the same, alkaline water electrolysis cell, alkaline water electrolysis device, hydrogen production method, and method for manufacturing membrane for hydrogen production
Patent Information
- Application Number
- CN202580021080.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-21
- Publication Date
- 2026-10-20
AI Technical Summary
[0046]本发明的制氢用隔膜在组装碱性水电解池时的尺寸稳定性优异,并且离子传导性也优异。并且,根据本发明的制氢用隔膜的制造方法,能够适当地制造本发明的制氢用隔膜。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a diaphragm for hydrogen production, an alkaline water electrolysis component using the diaphragm for hydrogen production, an alkaline water electrolysis cell, an alkaline water electrolysis apparatus, a method for producing hydrogen, and a method for manufacturing the diaphragm for hydrogen production. Background Technology
[0002] Hydrogen is a clean energy source that does not emit carbon dioxide, and it can be used as fuel for fuel cells in fuel cell vehicles or home fuel cells. One known method for producing hydrogen is alkaline water electrolysis, which uses a highly concentrated alkaline aqueous solution as the electrolyte. If alkaline water electrolysis is performed using a power generation system that utilizes renewable energy sources, hydrogen can be produced without emitting carbon dioxide. Therefore, hydrogen is receiving increasing attention as a fundamental energy source for a sustainable society.
[0003] In alkaline water electrolysis, to prevent the formation of gaseous hydrogen bubbles (2H₂O + 2e⁻) at the cathode... - →H2+2OH - It moves towards the anode side and prevents the formation of gaseous oxygen (4OH-) bubbles at the anode. - →O2 + 2H2O + 4e - The anode moves towards the cathode side, and a gas-barrier diaphragm is placed between the cathode and the anode. Besides gas barrier properties, this diaphragm is also required to prevent OH- from entering the cathode. - The conductivity of ions (hydroxyl ions) that permeate from the cathode side to the anode side. Therefore, porous membranes (microporous membranes) formed of organic polymer materials are used in the membranes of alkaline water electrolysis.
[0004] Porous membranes for alkaline water electrolysis can be formed using a wet phase separation method. In wet phase separation, firstly, an organic polymer, which is a constituent material of the porous membrane, is dissolved in a solvent (good solvent) capable of dissolving the organic polymer to prepare a casting solution, and a coating of this casting solution is formed. Next, the coating is immersed in a solvent (poor solvent, coagulation bath) that does not dissolve the organic polymer but is miscible with the good solvent. If the proportion of good solvent in the coating decreases through this immersion, phase separation occurs between the organic polymer and the solvent, and the organic polymer gels (coagulates), thereby obtaining a porous membrane.
[0005] To improve the mechanical strength of porous membranes, porous supports such as inorganic or woven fabrics can be incorporated into the casting solution. In the presence of these porous supports, the aforementioned phase separation occurs, transforming the organic polymers in the impregnated casting solution into a porous structure. This results in a porous membrane where the porous support and the porous structure of the organic polymer are integrated. Furthermore, by including hydrophilic inorganic particles in the membrane, gas barrier properties are improved, and alkaline aqueous solutions can be effectively penetrated into the membrane, further enhancing ion conductivity.
[0006] As such a porous membrane, Patent Document 1 describes, for example, a membrane comprising a porous support and a first porous layer and a second porous layer respectively disposed on one side and the other side of the porous support. In this membrane, the porous support has a thickness of 150 μm or less, the membrane thickness is less than 250 μm, and the porous layers can contain hydrophilic inorganic particles. According to the technology described in Patent Document 1, a membrane with sufficient mechanical properties and improved ion conductivity can be provided.
[0007] Previous technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent Publication No. 2023-531792 Summary of the Invention
[0010] The technical problem to be solved by the invention
[0011] In recent years, from the perspective of improving hydrogen production efficiency and endowing alkaline water electrolysis systems with renewable energy adaptability, research and development are being promoted on high-pressure alkaline water electrolysis systems (also known as "pressurized alkaline water electrolysis systems" because they operate under pressures of more than 5 bar relative to atmospheric pressure (about 1 bar)).
[0012] As described in Patent Document 1, porous membranes used in conventional alkaline water electrolysis systems operating at atmospheric pressure are punched into square or rectangular shapes for application, thereby exhibiting sufficient mechanical quality and improved ion conductivity. However, in alkaline water electrolysis systems capable of operating at pressure, to prevent component damage, the membranes and electrodes are punched into circular shapes with superior pressure resistance. According to the researchers of the present invention, when assembled into an electrolytic cell, conventional porous membranes such as those described in Patent Document 1 can cause electrolyte leakage and current leakage, thereby hindering the operation of the pressurized alkaline water electrolysis system.
[0013] The inventors have repeatedly studied the aforementioned problems that arise when assembling a circular porous diaphragm into the electrolytic cell of a pressurized alkaline water electrolysis system. The results show that the circular porous diaphragm is prone to deformation during the assembly process into the electrolytic cell, which can hinder the operation of the pressurized alkaline water electrolysis system.
[0014] The objective of this invention is to provide a diaphragm for hydrogen production that exhibits excellent dimensional stability and ion conductivity when assembled into an alkaline water electrolyzer, and a method for manufacturing the same.
[0015] Furthermore, the objective of this invention is to provide an alkaline water electrolysis component, an alkaline water electrolysis cell, an alkaline water electrolysis apparatus, and a method for producing hydrogen using the diaphragm for hydrogen production of this invention.
[0016] means for solving technical problems
[0017] The aforementioned problems of the present invention are solved by the following means.
[0018] [1]
[0019] A membrane for hydrogen production includes a woven fabric support and a porous material containing an organic polymer, wherein... The calendering ratio of the above-mentioned woven fabric support, calculated by the following formula, is 73% or less.
[0020] Rolling ratio = {d2 / (2×d1)}×100%
[0021] In the above formula, d1 represents the fiber diameter of the woven fabric support, and d2 represents the thickness of the woven fabric support.
[0022] [2]
[0023] According to the hydrogen production diaphragm described in [1], wherein, The fiber diameter d1 of the above-mentioned woven fabric support is less than 180μm.
[0024] [3]
[0025] According to the hydrogen production diaphragm described in [1] or [2], wherein, The thickness d2 of the woven fabric support is less than 250 μm.
[0026] [4]
[0027] The hydrogen production diaphragm according to any one of [1] to [3], wherein, The material of the woven fabric support includes at least one of polyphenylene sulfide and polyether ether ketone.
[0028] [5]
[0029] The hydrogen production diaphragm according to any one of [1] to [4], wherein, The aforementioned organic polymers include at least one of polysulfone, polyethersulfone, and polyphenylsulfone.
[0030] [6]
[0031] An alkaline water electrolysis device comprising a diaphragm for hydrogen production as described in any one of [1] to [5].
[0032] [7]
[0033] An alkaline water electrolyzer includes a diaphragm for hydrogen production as described in any one of [1] to [5] or an alkaline water electrolysis component as described in [6].
[0034] [8]
[0035] An alkaline water electrolysis device, comprising the alkaline water electrolysis cell described in [7].
[0036] [9]
[0037] A method for producing hydrogen, comprising: The alkaline water electrolysis device described in [8] is operated under a pressure of 5 bar or higher.
[0038]
[10]
[0039] A method for producing hydrogen, comprising: The alkaline water electrolysis device described in [8] is operated under a pressure of 50 mbar or more applied from the hydrogen production side to the oxygen production side.
[0040]
[11]
[0041] A method for manufacturing a hydrogen production diaphragm, wherein the hydrogen production diaphragm is any one of [1] to [5], and the method for manufacturing the hydrogen production diaphragm includes: In a coating formed by dissolving an organic polymer, a woven fabric support obtained by calendering and having a calendering ratio of 73% or less as calculated by the following formula is placed in the coating, a porous material containing the aforementioned organic polymer is formed by wet phase separation.
[0042] Rolling ratio = {d2 / (2×d1)}×100%
[0043] In the above formula, d1 represents the fiber diameter of the woven fabric support, and d2 represents the thickness of the woven fabric support.
[0044] Furthermore, in this invention, the numerical range represented by “~” refers to the range encompassed by the values recorded before and after “~” as the lower and upper limits.
[0045] Invention Effects
[0046] The hydrogen production diaphragm of the present invention exhibits excellent dimensional stability and ion conductivity when assembled into an alkaline water electrolyzer. Furthermore, the hydrogen production diaphragm of the present invention can be suitably manufactured using the manufacturing method of the present invention.
[0047] Furthermore, the alkaline water electrolysis component of the present invention exhibits excellent dimensional stability and ion conductivity when assembling an alkaline water electrolysis cell.
[0048] Furthermore, when assembling the pressurized alkaline water electrolysis cell and alkaline water electrolysis apparatus of the present invention, the hydrogen production diaphragm of the present invention will not protrude from the electrolysis cell, thereby preventing electrolyte leakage and gas leakage caused by defects, and due to its excellent ion conductivity, it is able to produce hydrogen.
[0049] Furthermore, in the hydrogen production method of the present invention, hydrogen can be efficiently produced using the alkaline water electrolysis apparatus of the present invention. Attached Figure Description
[0050] Figure 1 This is a schematic schematic cross-sectional view of a woven fabric support to illustrate the thickness d2 of the woven fabric support.
[0051] Figure 2 This is a schematic diagram illustrating one embodiment of an alkaline water electrolysis system.
[0052] Figure 3 This is a schematic diagram illustrating another embodiment of an alkaline water electrolysis system.
[0053] Figure 4 This is a schematic diagram illustrating yet another embodiment of an alkaline water electrolysis system. Detailed Implementation
[0054] [Separator for hydrogen production]
[0055] The hydrogen production diaphragm of the present invention includes a woven fabric support and a porous material containing an organic polymer, wherein the calendering ratio of the woven fabric support, calculated by the formula described later, is 73% or less.
[0056] Regarding the hydrogen production diaphragm of the present invention, in the structure of the hydrogen production diaphragm including a woven fabric support and a porous material containing an organic polymer, by setting the calendering ratio of the woven fabric support, calculated by the formula described later, to 73% or less, excellent dimensional stability under tension and excellent ion conductivity can be achieved in the hydrogen production diaphragm. Therefore, when the hydrogen production diaphragm of the present invention is applied to an alkaline water electrolyzer, hydrogen can be produced without electrolyte leakage or gas leakage caused by defects.
[0057] The specific structure of the hydrogen production diaphragm of the present invention, which consists of a woven fabric support and a porous material containing an organic polymer, is not particularly limited as long as the calendering ratio of the woven fabric support calculated by the formula described later is 73% or less and the diaphragm has the desired gas barrier properties and hydroxide ion permeability (ion conductivity) required for a hydrogen production diaphragm.
[0058] For example, the hydrogen production diaphragm of the present invention can be configured as a structure comprising a woven fabric support and a porous material containing an organic polymer disposed in at least one of the outer surface and pores of the woven fabric support. The structure in which the porous material containing an organic polymer is disposed in the outer surface and pores of the woven fabric support can be obtained, for example, by the manufacturing method of the hydrogen production diaphragm of the present invention described later.
[0059] Furthermore, "outer surface of the woven fabric support" refers to the surface of the membrane when the woven fabric support is viewed from a macroscopic perspective as a membrane of thickness, and "voids of the woven fabric support" refers to the gaps between the fibers constituting the woven fabric support. As a structure in which a porous material containing an organic polymer is disposed in at least one of the outer surface and voids of the woven fabric support, the structure can be appropriately adjusted within the range where the hydrogen production membrane has the target gas barrier and ion conductivity. For example, a structure in which the aforementioned porous material is disposed only on the outer surface of the woven fabric support can be used. In this case, a structure in which the aforementioned porous material is disposed only on one side of the woven fabric support can be used, or a structure in which the aforementioned porous material is disposed on both sides can be used. Furthermore, a structure in which the aforementioned porous material is disposed only in the voids of the woven fabric support can also be used. Additionally, a structure in which the aforementioned porous material is disposed in a portion of the outer surface and a portion of the voids of the woven fabric support can also be used. In this invention, this configuration is also included in a structure in which a porous material containing an organic polymer is disposed in at least one of the outer surface and voids of the woven fabric support. Preferably, the structure in which the above-mentioned porous material is disposed in the entirety and the voids of the outer surface of the woven fabric support.
[0060] The constituent materials of the hydrogen production diaphragm of the present invention will be described in detail below.
[0061] (Woven fabric support)
[0062] The woven fabric support is a woven fabric that functions as a support for reinforcing the hydrogen production diaphragm to improve its mechanical strength. In the hydrogen production diaphragm of the present invention, the calendering ratio calculated by the following formula is 73% or less.
[0063] Rolling ratio = {d2 / (2×d1)}×100%
[0064] In the above formula, d1 represents the fiber diameter of the woven fabric support, and d2 represents the thickness of the woven fabric support.
[0065] In the calculation of the rolling ratio, the units of d1 and d2 only need to be the same. For example, the rolling ratio can be calculated by setting the units of d1 and d2 to μm and substituting them into the above formula.
[0066] d1 and d2 are values determined and calculated using the following method.
[0067] The fiber diameter d1 of the woven fabric support is used as the observation surface. The surface perpendicular to the thickness direction of the woven fabric support (i.e., the surface or back of the woven fabric support) is used as the observation surface. The arithmetic mean of the fiber diameters at 20 locations at equidistant points from two adjacent intersections (the intersections of fibers) is calculated for the optical microscope image observed by transmitted light in a 1 mm square field of view.
[0068] The thickness d2 of the woven fabric support is calculated using a digital micrometer (e.g., manufactured by MESSMER BUCHEL) for a 10cm square woven fabric support, by determining the thickness at the fiber intersections. Figure 1 The arithmetic mean of the thicknesses at 20 intersection points (d2) of parallel F1 and meridian F2 shown (reference) Figure 1 ).
[0069] In addition, regarding the woven fabric support d1 and d2 in the hydrogen production diaphragm, the woven fabric support can be removed from the hydrogen production diaphragm using a solvent that can dissolve the organic polymer contained in the porous material, and the removed woven fabric support can be measured and calculated using the above method.
[0070] From the viewpoint of further suppressing deformation during the assembly of the alkaline water electrolysis cell, the upper limit of the above-mentioned calendering ratio is preferably 70% or less. Regarding the lower limit of the above-mentioned calendering ratio, for the structure of woven fabrics, it is 50% or more.
[0071] Therefore, the range of the above-mentioned rolling ratio is usually 50 to 73%, preferably 55 to 73%, and more preferably 60 to 70% from the viewpoint of further suppressing deformation when assembling alkaline water electrolysis cells.
[0072] The fiber diameter d1 of the woven fabric support is preferably less than 180 μm, more preferably 30 to 180 μm, and even more preferably 35 to 150 μm.
[0073] The thickness d2 of the woven fabric support is preferably less than 250 μm, more preferably 40 to 250 μm, and even more preferably 50 to 210 μm.
[0074] The opening ratio of the woven fabric support is preferably 30-80%, more preferably 40-70%. The opening ratio refers to the proportion of the area occupied by voids per unit area when the woven fabric support is observed from a plane.
[0075] The woven fabric support in the hydrogen production diaphragm preferably has a calendering ratio of 50-73%, a fiber diameter d1 of 30-180 μm, and a woven fabric support thickness d2 of 40-250 μm; more preferably, a calendering ratio of 50-73%, a fiber diameter d1 of 30-180 μm, and a woven fabric support thickness d2 of 50-210 μm; more preferably, a calendering ratio of 50-73%, a fiber diameter d1 of 35-150 μm, and a woven fabric support thickness d2 of 40-250 μm; and more preferably, a calendering ratio of 50-73%, a fiber diameter d1 of 35-150 μm, and a woven fabric support thickness d2 of 50-210 μm.
[0076] Furthermore, the woven fabric support in the hydrogen production diaphragm preferably has a calendering ratio of 55-73%, a fiber diameter d1 of 30-180 μm, and a woven fabric support thickness d2 of 40-250 μm; more preferably, a calendering ratio of 55-73%, a fiber diameter d1 of 30-180 μm, and a woven fabric support thickness d2 of 50-210 μm; more preferably, a calendering ratio of 55-73%, a fiber diameter d1 of 35-150 μm, and a woven fabric support thickness d2 of 40-250 μm; and more preferably, a calendering ratio of 55-73%, a fiber diameter d1 of 35-150 μm, and a woven fabric support thickness d2 of 50-210 μm.
[0077] Furthermore, the woven fabric support in the hydrogen production diaphragm preferably has a calendering ratio of 60-70%, a fiber diameter d1 of 30-180 μm, and a woven fabric support thickness d2 of 40-250 μm; more preferably, a calendering ratio of 60-70%, a fiber diameter d1 of 30-180 μm, and a woven fabric support thickness d2 of 50-210 μm; more preferably, a calendering ratio of 60-70%, a fiber diameter d1 of 35-150 μm, and a woven fabric support thickness d2 of 40-250 μm; and more preferably, a calendering ratio of 60-70%, a fiber diameter d1 of 35-150 μm, and a woven fabric support thickness d2 of 50-210 μm.
[0078] There are no particular restrictions on the materials used for woven fabric supports. Examples include polypropylene (PP), polyethylene, polysulfone, polyphenylene sulfide (PPS), polyamide, polyethersulfone, polyphenylene sulfone, polyethylene terephthalate, polyether ether ketone (PEEK), sulfonated polyether ether ketone, trichlorofluoroethylene, copolymers of ethylene with tetrafluoroethylene or trifluorochloroethylene, polyimide, polyetherimide, and meta-aramid.
[0079] As the material for the woven fabric support, the above-mentioned materials preferably include at least one of polypropylene (PP), polyphenylene sulfide (PPS) and polyether ether ketone (PEEK). From the viewpoint of further suppressing deformation during the assembly of the alkaline water electrolysis cell, it is more preferable to include at least one of polyphenylene sulfide (PPS) and polyether ether ketone (PEEK).
[0080] <Method for preparing a woven fabric support having the above-mentioned calendering ratio>
[0081] The woven fabric support having the above-mentioned calendering ratio can be prepared by calendering a commercially available woven fabric in such a way as to achieve the above-mentioned calendering ratio.
[0082] The opening ratio of commercially available woven fabrics subjected to calendering is preferably 30-80%, more preferably 40-70%. The opening ratio refers to the proportion of the area occupied by voids per unit area when the woven fabric support is viewed from a plane.
[0083] The calendering process is preferably carried out by a calendering apparatus.
[0084] As a calendering device, supercalenders, gloss calenders, machine calenders, soft calenders, etc., can be used. Calendering is preferably performed using two rollers. By passing the woven fabric support through the gap between the two rollers, the thickness d2 of the woven fabric support can be reduced through pressure, shear force, and heat, thereby adjusting the calendering ratio of the woven fabric support.
[0085] There are no particular limitations on the materials used to make the rollers. For example, metal rollers are preferred, and rollers with a protective layer formed by melting nickel, chromium, ceramics, etc. on the surface of rollers such as steel are even more preferred. Preferably, the surface is polished to have a mirror finish.
[0086] Calendering can be performed without heating the rollers, but heating can further reduce the thickness d2 of the woven fabric support, so it is preferred. The surface temperature of the rollers is preferably 90–300°C, more preferably 140–250°C, and even more preferably 160–210°C.
[0087] The linear pressure (roll gap pressure) of the roll gap between the two rolls is preferably 10 to 400 kgf / cm, more preferably 20 to 200 kgf / cm, and even more preferably 40 to 120 kgf / cm.
[0088] The processing speed (transfer speed) for calendering is preferably 5 to 60 m / min, more preferably 10 to 60 m / min, and even more preferably 15 to 40 m / min.
[0089] The number of times the roller passes through the gap needs to be more than once, preferably 1 to 5 times, and more preferably 2 to 5 times.
[0090] The surface roughness of the metal roller is preferably 3 μm or less, more preferably 1 μm or less, and even more preferably 0.5 μm or less. The actual lower limit is 0.1 μm or more.
[0091] (Porous materials containing organic polymers)
[0092] Porous materials containing organic polymers (hereinafter also referred to as "porous materials") have the function of preventing hydrogen and oxygen from passing through while allowing hydroxide ions to pass through.
[0093] -Organic polymers-
[0094] As organic polymers contained in porous materials, various organic polymers that can be applied to wet phase separation can be used.
[0095] Organic polymers can be selected from, for example, fluoropolymers, olefin resins, polyester resins, aromatic hydrocarbon resins, etc.
[0096] The preferred fluororesin is one selected from polyvinylidene fluoride (PVDF) and polytetrafluoroethylene.
[0097] Polypropylene resin is preferred as the olefin resin mentioned above.
[0098] The preferred polyester resin is one selected from polyethylene terephthalate, polybutylene terephthalate, and polybutylene naphthalate.
[0099] Polystyrene resin is preferred as the aforementioned aromatic hydrocarbon resin.
[0100] Other preferred organic polymers include polysulfone (PSf), polyethersulfone (PES), polyphenylene sulfide, polyphenylene sulfone (PPSf), polyacrylate, polyetherimide, polyimide, and polyamideimide.
[0101] Organic polymers can be used alone or in combination of two or more.
[0102] The organic polymer more preferably includes at least one of polyvinylidene fluoride (PVDF), polysulfone (PSf), polyethersulfone (PES), and polyphenylsulfone (PPSf), and even more preferably includes at least one of polysulfone (PSf), polyethersulfone (PES), and polyphenylsulfone (PPSf).
[0103] The mass-average molecular weight (Mw) of the organic polymer is not particularly limited. Considering the operability of the casting solution described later and the mechanical strength of the obtained hydrogen production diaphragm, it can be set to, for example, 10,000 to 500,000, preferably 20,000 to 300,000. Mw can be determined under the following conditions.
[0104] Device: HLC-8220GPC (manufactured by TOSOH CORPORATION)
[0105] Detector: Differential refractometer (RI (Refractive Index) detector)
[0106] Pre-support: TSKGUARDCOLUMN HXL-L 6mm×40mm (manufactured by TOSOH CORPORATION)
[0107] Sample side columns: Connect the following three columns directly in sequence (all manufactured by TOSOH CORPORATION).
[0108] ·TSK-GEL GMHXL 7.8mm×300mm
[0109] ·TSK-GEL G4000HXL 7.8mm×300mm
[0110] ·TSK-GEL G2000HXL 7.8mm×300mm
[0111] Reference side pillar: TSK-GEL G1000HXL 7.8mm×300mm
[0112] Thermostatic bath temperature: 40℃
[0113] Mobile phase: THF (tetrahydrofuran)
[0114] Sample-side mobile phase flow rate: 1.0 mL / min
[0115] Reference side mobile phase flow rate: 1.0 mL / min
[0116] Sample concentration: 0.1% by mass
[0117] Sample injection volume: 100 μL
[0118] Data acquisition time: 5 to 45 minutes after sample injection
[0119] Sampling interval: 300 milliseconds
[0120] The content of organic polymer in the porous material is preferably 5-50% by mass, more preferably 5-40% by mass, even more preferably 7-30% by mass, and especially preferably 9-25% by mass.
[0121] -Hydrophilic inorganic particles-
[0122] Porous materials containing organic polymers can contain hydrophilic inorganic particles. The hydrophilic inorganic particles are preferably selected from metal oxides and metal hydroxides.
[0123] The metal oxides mentioned above are preferably selected from zirconium oxide, titanium oxide, bismuth oxide, cerium oxide, and magnesium oxide.
[0124] The preferred metal hydroxides are those selected from zirconium hydroxide, titanium hydroxide, bismuth hydroxide, cerium hydroxide, and magnesium hydroxide.
[0125] In addition to particles selected from metal oxides and metal hydroxides, barium sulfate particles can also be used as hydrophilic inorganic particles.
[0126] Hydrophilic inorganic particles can be used alone or in combination of two or more.
[0127] The particle size of the hydrophilic inorganic particles is preferably 0.05–2.00 μm, more preferably 0.1–1.50 μm, even more preferably 0.15–1.00 μm, and even more preferably 0.20–1.00 μm. This particle size is the median particle size (D50), which refers to the particle size at which the cumulative distribution reaches 50% when the total volume of particles is set to 100% in the cumulative distribution, as determined by laser diffraction / scattering.
[0128] When the porous material contains hydrophilic inorganic particles, the content of hydrophilic inorganic particles in the porous material is preferably 50-95% by mass, more preferably 60-95% by mass, even more preferably 70-93% by mass, and especially preferably 75-91% by mass.
[0129] When the porous material contains hydrophilic inorganic particles, the ratio of the content of hydrophilic inorganic particles to the content of organic polymer in the porous material (hydrophilic inorganic particles / organic polymer), by mass ratio, is preferably 10 / 1 to 1 / 1, more preferably 9 / 1 to 2 / 1, even more preferably 8 / 1 to 3 / 1, even more preferably 7 / 1 to 4 / 1, and even more preferably 6.5 / 1 to 5 / 1.
[0130] When the hydrogen production diaphragm of the present invention is manufactured using the manufacturing method of the hydrogen production diaphragm of the present invention described later, a certain amount of the good solvent described later in the casting solution inevitably remains in the porous material. As a result, the total content of the good solvent in the porous material is generally 0.01 to 5.00% by mass.
[0131] The thickness of the hydrogen production diaphragm of the present invention is preferably 60–300 μm, more preferably 70–270 μm, and even more preferably 80–250 μm. This thickness is the arithmetic mean of 20 measurements taken at 20-point intervals in a cross-section obtained by shaving a section cut from the hydrogen production diaphragm with a razor, at a magnification (e.g., 400x) that allows the diaphragm cross-section to be contained within a single field of view. These measurements assume the absence of pores (assuming the pores are filled with organic polymers).
[0132] The pore size of the diaphragm for hydrogen production in this invention is only small enough to prevent the recombination of hydrogen and oxygen by avoiding cross-permeation of gases, and to be large enough to reliably and efficiently transport hydroxide ions from the cathode to the anode.
[0133] From the above perspective, the pore size of the diaphragm for hydrogen production of the present invention is preferably 50–1000 nm, more preferably 100–800 nm, and even more preferably 150–600 nm. The above pore size is determined by the following method: A diaphragm cut to a diameter of 1 cm is immersed in pure water at room temperature (25°C) for 24 hours. Then, the mean flow pore size is calculated using Palm Porometry, manufactured by Porometer.
[0134] From the viewpoint of exhibiting excellent ion permeability and excellent gas barrier properties, the porosity of the hydrogen production diaphragm of the present invention is preferably 30-70%, more preferably 40-60%. This porosity can be calculated by the following method: First, the diaphragm is cut into a specified area S and immersed in pure water at room temperature (25°C) for 24 hours. Then, excess water droplets adhering to the surface are wiped off, and the weight w1 and thickness d are measured. It is then dried in an oven at 90°C for 24 hours, and the weight w2 is measured again. The porosity is calculated using the following formula: Formula: 1 - (w1 - w2) / (S × d)
[0135] From the viewpoint of the required permeability of hydroxide ions for membranes used in alkaline water electrolysis, the ion resistance of the hydrogen production membrane of the present invention is preferably 0.01 to 0.10 Ω·cm. 2 More preferably, it is 0.01 to 0.08 Ω·cm. 2 More preferably, it is 0.01–0.07 Ω·cm. 2 .
[0136] The ion resistance is a value measured by alternating current impedance method when the circularly cut diaphragm of the present invention is placed in an electrolytic cell and subjected to an alternating current impedance method at 90°C. For details, please refer to the examples described below.
[0137] From the viewpoint of the material balance of the electrolyte on the cathode and anode sides required for alkaline water electrolysis diaphragms, the water permeability of the hydrogen production diaphragm of the present invention is preferably 100–2000 mL / (h·m). 2 From the viewpoint that it is not necessary to take measures to change the permeation rate of the electrolyte on the anode and cathode sides in alkaline water electrolysis cells, a value of 100 to 1000 mL / (h·m) is more preferable. 2 ·bar).
[0138] The permeability is obtained by placing the circularly cut diaphragm of the present invention in a filter holder, and allowing a 30% by mass potassium hydroxide aqueous solution to pass through the circular diaphragm for 30 seconds at 90°C and a gauge pressure of 1 bar. The volume (mL) of the liquid at this time is measured and the unit is converted to calculate the value.
[0139] The hydrogen production diaphragm of the present invention can be used without particular limitation as long as it is a hydrogen production diaphragm. It can be preferably used as a diaphragm in an alkaline water electrolysis system (alkaline water electrolysis diaphragm), and more preferably used as a diaphragm in a pressurized alkaline water electrolysis system (pressurized alkaline water electrolysis diaphragm).
[0140] The diaphragm for hydrogen production of the present invention can be rolled into a roll from a long sheet, or it can be pre-cut into a specified shape according to the application, device, etc.
[0141] Furthermore, the hydrogen production diaphragm of the present invention can be stored and preserved by immersion in a preservation solution such as pure water. Alternatively, the hydrogen production diaphragm of the present invention can be stored and preserved as a dry membrane without immersion in a preservation solution.
[0142] [Manufacturing method of diaphragm for hydrogen production]
[0143] The method for manufacturing a hydrogen production diaphragm of the present invention (hereinafter also referred to as "the manufacturing method of the present invention") includes: forming a porous material containing the above-mentioned organic polymer by wet phase separation in a coating formed by a casting solution obtained from a dissolved organic polymer, wherein a woven fabric support obtained by calendering and whose calendering ratio calculated by the following formula is 73% or less is disposed in the coating.
[0144] Rolling ratio = {d2 / (2×d1)}×100%
[0145] In the above formula, d1 represents the fiber diameter of the woven fabric support, and d2 represents the thickness of the woven fabric support. The meanings of d1 and d2 are the same as those in the hydrogen production diaphragm described above.
[0146] Through this process, the hydrogen production diaphragm of the present invention can be obtained, which is composed of the above-mentioned woven fabric support and a porous material containing the above-mentioned organic polymer disposed in at least one of the outer surface and pores of the woven fabric support.
[0147] Furthermore, regarding the woven fabric support obtained by calendering and having a calendering ratio of 73% or less calculated by the above formula (hereinafter, also simply referred to as "woven fabric support"), it is sufficient to perform calendering treatment by the method described in the <Preparation Method of Woven Fabric Support Having the Above Calendering Ratio> for the above-mentioned hydrogen production diaphragm to obtain a woven fabric support with a calendering ratio of 73% or less calculated by the above formula. Regarding the calendering treatment, the calendering treatment described in the <Preparation Method of Woven Fabric Support Having the Above Calendering Ratio> can be applied.
[0148] (Casting solution)
[0149] The casting solution can be any solution of an organic polymer that is a constituent material of porous materials. It can contain organic polymers and solvents, and can also contain hydrophilic inorganic particles.
[0150] Regarding the organic polymer contained in the casting solution, the organic polymer described above for hydrogen production diaphragms can be applied.
[0151] Furthermore, regarding the hydrophilic inorganic particles that may be contained in the casting solution, the hydrophilic inorganic particles described above in the hydrogen production diaphragm can be applied.
[0152] -solvent-
[0153] In the manufacturing method of the present invention, the casting solution in the wet phase separation can be any solvent (good solvent) capable of dissolving the above-mentioned organic polymer, and preferably miscible with water.
[0154] The solvent is preferably selected from N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), N-butylpyrrolidone (NBP), N,N-dimethylformamide (DMF), formamide, dimethyl sulfoxide (DMSO), N,N-dimethylacetamide (DMAC), acetonitrile, and mixtures thereof, and more preferably at least one of NMP and NBP.
[0155] The solvent content in the above casting solution is preferably 20-95% by mass, more preferably 25-90% by mass, even more preferably 30-80% by mass, even more preferably 30-70% by mass, even more preferably 32-60% by mass, and even more preferably 35-50% by mass.
[0156] -Organic polymers-
[0157] The content of organic polymer in the above casting solution is preferably 2-30% by mass, more preferably 4-20% by mass, even more preferably 5-15% by mass, and even more preferably 6-12% by mass.
[0158] -Hydrophilic inorganic particles-
[0159] Furthermore, the hydrophilic inorganic particles are particles that are dispersed and do not dissolve in the casting solution. In this invention, this dispersion is also referred to as the casting solution. That is, the "solution" of the casting solution means that the organic polymer is dissolved in a solvent.
[0160] When the casting solution contains hydrophilic inorganic particles, the content of hydrophilic inorganic particles in the casting solution is preferably 20-95% by mass, more preferably 25-92% by mass, even more preferably 30-90% by mass, and particularly preferably 35-88% by mass.
[0161] -Other ingredients-
[0162] The casting solution described above may contain components other than those listed above (solvents, organic polymers, and hydrophilic inorganic particles). For example, to control the formation of fine pores in wet phase separation, it may contain polyethylene glycol, polyethylene oxide, polypropylene glycol, ethylene glycol, tripropylene glycol, glycerin, polyols, dibutyl phthalate, diethyl phthalate, undecyl phthalate, isononanoic acid or neodecanoic acid, polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl acetate, polyethyleneimine, polyacrylic acid, methylcellulose, dextran, calcium chloride, magnesium chloride, and lithium chloride, etc.
[0163] When the casting solution contains other components and contains hydrophilic inorganic particles, the total content of the other components in the casting solution is preferably 0.1 to 15% by mass, more preferably 0.2 to 10% by mass, and even more preferably 0.5 to 5% by mass.
[0164] When the casting solution contains other components but does not contain hydrophilic inorganic particles, the total content of the other components in the casting solution is preferably 1 to 25% by mass, more preferably 5 to 25% by mass, and even more preferably 7 to 20% by mass.
[0165] <Formation of Porous Materials Based on Wet Phase Separation>
[0166] In the manufacturing method of the present invention, a hydrogen production diaphragm is manufactured by forming a porous material through wet phase separation while a woven fabric support is disposed in a coating film formed from a casting liquid obtained by dissolving an organic polymer. In the wet phase separation, a woven fabric support is placed on a coating film formed by casting the casting liquid onto a substrate, and the woven fabric support is immersed in the coating film, such that the woven fabric support is impregnated with the casting liquid, preferably completely impregnated. Next, the woven fabric support impregnated with the casting liquid is immersed in a solvent (poor solvent, coagulation bath) that does not dissolve the organic polymer and is compatible (miscible) with the good solvent. If the proportion of good solvent in the coating film of the casting liquid decreases through this immersion, phase separation (liquid-induced phase separation) occurs between the organic polymer and the solvent, and the organic polymer gels (coagulates), thereby obtaining the hydrogen production diaphragm of the present invention, which forms a porous material containing an organic polymer. Thus, a structure is formed in which a porous material containing an organic polymer is disposed in at least one of the outer surface and the pores of the woven fabric support. Furthermore, the impregnation of the woven fabric support containing the casting solution into a poor solvent can be performed in the aforementioned state with the substrate attached. In this case, after liquid-induced phase separation, the substrate is peeled off, thereby obtaining the hydrogen production diaphragm of the present invention.
[0167] As a poor solvent, for example, water or a mixture of water-miscible organic solvents or water-soluble polymers can be used. Examples of hydrophilic organic solvents include aprotic solvents such as N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and dimethylacetamide (DMAC), as well as alcohol solvents such as ethanol, propanol, or isopropanol. Examples of water-soluble polymers include polyvinylpyrrolidone (PVP) or polyvinyl alcohol (PVA).
[0168] In the above, water is preferred as a poor solvent.
[0169] Before immersing the membrane in the aforementioned unsuitable solvent, vapor-based phase separation (vapor-induced phase separation) can be achieved by exposing it to the vapor of the solvent. By performing vapor-induced phase separation, the pore size of the surface layer can be adjusted more precisely. Therefore, in the aforementioned wet phase separation, vapor-induced phase separation and liquid-induced phase separation can also be combined.
[0170] In the hydrogen production diaphragm obtained by the manufacturing method of the present invention, a certain amount of good solvent from the casting solution used in the manufacturing inevitably remains. As a result, a hydrogen production diaphragm is provided in which the total content of good solvent in the porous material is 0.01 to 5.00% by mass.
[0171] Regarding the residual solvent content, it can be determined by gas chromatography or... after pre-drying the diaphragm at 40°C for 12 hours. 1 ¹H-NMR was used to quantify the content of the above-mentioned dried alkaline water electrolysis porous membrane in 100% by mass.
[0172] The hydrogen production diaphragm of the present invention can be used as a diaphragm in a method for producing hydrogen by electrolyzing an alkaline aqueous solution in an electrolytic cell. In particular, it can be preferably used as an alkaline water electrolysis diaphragm in the alkaline water electrolysis system described below.
[0173] [Alkaline water electrolysis]
[0174] The hydrogen production diaphragm of the present invention (hereinafter also referred to as "the diaphragm of the present invention") is used in alkaline water electrolysis between the cathode and the anode. Preferred embodiments of an alkaline water electrolysis system (also referred to as "the alkaline water electrolysis system of the present invention") in which the diaphragm of the present invention can be applied will be described, but the alkaline water electrolysis of the present invention is not limited to these embodiments.
[0175] Figure 2 This is a schematic diagram illustrating a preferred embodiment of the alkaline water electrolysis system of the present invention. Figure 2 In the alkaline water electrolysis system 10 shown, a cathode electrode 12 is disposed on one side of the diaphragm 11 of the present invention, and an anode electrode 13 is disposed on the other side. The diaphragm 11 and each electrode 12, 13 are immersed in a high-concentration alkaline aqueous solution 14 (preferably an aqueous solution of potassium hydroxide or sodium hydroxide). If current flows between the electrodes, electrons are supplied to the cathode side, and gaseous hydrogen (H2) (2H2O + 2e) is generated from the water. - →H2+2OH - The hydroxide ions (OH-) generated along with this hydrogen are - The oxygen (O2) moves towards the anode side through the diaphragm 11, where electrons are taken away to generate bubble-like oxygen (O2) (4OH). - →O2 + 2H2O + 4e - The cathode electrode 12 and anode electrode 13 described above are preferably composed of an electrode substrate (conductive material) and a catalyst layer on the electrode substrate. When a catalyst layer is included, the types of catalysts used in the cathode electrode 12 and anode electrode 13 may be the same or different.
[0176] Figure 2 In the alkaline water electrolysis system 10 shown, since the diaphragm 11 is separated from each electrode 12 and 13, the hydroxide ions have a long travel distance, which limits the improvement of ion conduction efficiency.
[0177] Figure 3 This is a schematic diagram illustrating another preferred embodiment of the alkaline water electrolysis system of the present invention. Figure 3The alkaline water electrolysis system 20 shown is in Figure 2 The alkaline water electrolysis system 10 shown is a system (zero-gap type) in which the diaphragm 11 is arranged in contact with each electrode 12, 13. Figure 3 In the alkaline water electrolysis system 20 shown, since the diaphragm 11 is in contact with each electrode 12 and 13, the movement distance of hydroxide ions is short, which is advantageous in terms of ion conduction efficiency.
[0178] Regarding pressurized alkaline water electrolysis systems, for example, examples can be cited in... Figure 3 The alkaline water electrolysis system shown is a system in which the structure and components of the alkaline water electrolysis system are appropriately adjusted to cope with pressurized operation (e.g., operation under pressurized conditions of 5 bar or higher). For example, a system in which the diaphragm 11 is shaped into a circular shape to withstand pressurized operation can be described. Furthermore, regarding other components, conventional components used in pressurized alkaline water electrolysis systems can be appropriately applied.
[0179] Figure 4 This is a schematic diagram illustrating another preferred embodiment of the alkaline water electrolysis system of the present invention. Figure 4 The alkaline water electrolysis system 30 shown is in the form of a membrane electrode assembly. Specifically, a cathode catalyst layer 32 is disposed on one side of the membrane 31 of the present invention, and an anode catalyst layer 33 is disposed on the other side. These catalyst layers are composed of a catalyst and its binder. Furthermore, a gas diffusion layer 34 is formed on the outer surface of these catalyst layers (the surface opposite to the side where the membrane 31 is disposed), thereby constituting the membrane electrode assembly. Figure 4 In this membrane electrode assembly, a bipolar plate 35 is formed on the outer side. An alkaline aqueous solution is supplied to the cathode catalyst layer 32 and the anode catalyst layer 33 of the membrane electrode assembly, electrically connecting and energizing the cathode catalyst layer 32 and the anode catalyst layer 33, thereby generating bubble-like hydrogen from the cathode catalyst layer 32 and bubble-like oxygen from the anode catalyst layer 33.
[0180] In the above-mentioned alkaline water electrolysis system, there are no particular restrictions on the structure of the cathode electrode, cathode catalyst layer, anode electrode, anode catalyst layer, etc., except for the diaphragm, and the usual components used in alkaline water electrolysis systems can be appropriately applied.
[0181] Thus, in one embodiment, the present invention provides an alkaline water electrolysis system in which the diaphragm of the present invention is assembled as a diaphragm in an alkaline water electrolysis system. Furthermore, in one embodiment, the present invention provides a method for manufacturing an alkaline water electrolysis system including the diaphragm of the present invention assembled as a diaphragm in an alkaline water electrolysis system.
[0182] [Alkaline water electrolysis components]
[0183] The alkaline water electrolysis component of the present invention includes the diaphragm of the present invention.
[0184] Specifically, the alkaline water electrolysis component of the present invention includes at least one of the diaphragm, catalyst, anode electrode, and cathode electrode of the present invention. Furthermore, the arrangement of including the diaphragm, anode electrode, and cathode electrode of the present invention is classified as the alkaline water electrolysis cell of the present invention, as described later.
[0185] Examples of alkaline water electrolysis components of the present invention that do not contain electrodes but contain catalysts include a method in which the catalyst is present only on one side of the membrane of the present invention and a method in which the catalyst is present on both sides of the membrane of the present invention.
[0186] As an example of the alkaline water electrolysis component of the present invention, which includes an anode electrode but not a cathode electrode, an example is a configuration where the anode electrode is provided on one side of the membrane of the present invention. In this configuration, a catalyst may or may not be present. If a catalyst is present, it may be provided only on one side of the membrane of the present invention, or it may be provided on both sides of the membrane of the present invention.
[0187] As an example of the alkaline water electrolysis component of the present invention, which includes a cathode electrode but not an anode electrode, a configuration in which the cathode electrode is provided on one side of the membrane of the present invention can be described. In this configuration, a catalyst may or may not be present. If a catalyst is present, it may be provided only on one side of the membrane of the present invention, or it may be provided on both sides of the membrane of the present invention.
[0188] [Alkaline water electrolysis cell]
[0189] The alkaline water electrolysis cell of the present invention includes the diaphragm of the present invention or the alkaline water electrolysis component of the present invention.
[0190] The "alkaline water electrolysis cell" includes a diaphragm and two electrodes (an anode electrode and a cathode electrode) separated by the diaphragm. In this configuration, an alkaline aqueous solution as an electrolyte can be present between the two electrodes (including the diaphragm of this invention), and the anode electrode and cathode electrode may further contain catalysts.
[0191] For example, in the case where the alkaline water electrolysis cell of the present invention includes the membrane of the present invention, the alkaline water electrolysis cell of the present invention can be manufactured by combining the membrane of the present invention with the anode electrode and the cathode electrode. In this case, the anode electrode and the cathode electrode can each contain a catalyst independently.
[0192] Furthermore, when the alkaline water electrolysis cell of the present invention includes the diaphragm and catalyst of the present invention but does not include electrodes, the alkaline water electrolysis cell of the present invention can be manufactured by combining it with an anode electrode and a cathode electrode. In this case, the catalyst can be included in the alkaline water electrolysis component of the present invention, or it can be separately included and combined with the alkaline water electrolysis component of the present invention, similar to the anode electrode or the cathode electrode. Additionally, in the alkaline water electrolysis cell of the present invention, the catalyst can be included on at least one side of the diaphragm of the present invention, or it can be included on both sides.
[0193] Furthermore, in the case where the alkaline water electrolysis cell of the present invention does not include a cathode electrode but includes the diaphragm and anode electrode of the present invention, the alkaline water electrolysis cell of the present invention can be manufactured by combining it with the cathode electrode. In this case, the anode electrode and the cathode electrode can each independently include a catalyst. Furthermore, the catalyst can be included in the alkaline water electrolysis component of the present invention, or it can be separately included and combined with the alkaline water electrolysis component of the present invention, similar to the cathode electrode.
[0194] Furthermore, in the case where the alkaline water electrolysis cell of the present invention does not include an anode electrode but includes the diaphragm and cathode electrode of the present invention, the alkaline water electrolysis cell of the present invention can be manufactured by combining it with the anode electrode. In this case, the anode electrode and the cathode electrode can each independently include a catalyst. Furthermore, the catalyst can be included in the alkaline water electrolysis component of the present invention, or it can be separately included and combined with the alkaline water electrolysis component of the present invention, similar to the anode electrode.
[0195] [Alkaline water electrolysis device]
[0196] The alkaline water electrolysis device of the present invention includes the alkaline water electrolysis cell of the present invention.
[0197] The alkaline water electrolysis apparatus of the present invention, by supplementing the necessary components and structures with the structure of the alkaline water electrolysis cell according to the present invention, is able to produce hydrogen as described in the alkaline water electrolysis system above.
[0198] Methods for producing hydrogen
[0199] As a method for producing hydrogen according to the present invention, a preferred method is one that includes operating the alkaline water electrolysis apparatus of the present invention at a pressure of 5 bar or higher.
[0200] In this invention, "operation under pressure of 5 bar or more" means operating the system while controlling the pressure of the gas flow generated from each electrode chamber through a pressure control valve to apply a pressure of 5 bar or more to at least one of the cathode electrode chamber and the anode electrode chamber (which may be both). Furthermore, in an alkaline water electrolysis system, the electrolytic cell containing the cathode electrode on the side of the electrolytic cell separated by the diaphragm is called the cathode electrode chamber, and the electrolytic cell containing the anode electrode on the side is called the anode electrode chamber.
[0201] The pressure applied to at least one of the cathode electrode chamber and the anode electrode chamber is preferably 5 to 500 bar, more preferably 10 to 300 bar, and even more preferably 20 to 100 bar. It is also preferable to apply the above pressure to both the cathode electrode chamber and the anode electrode chamber.
[0202] The diaphragm of the present invention included in the alkaline water electrolysis apparatus of the present invention can be preferably applied to a pressurized alkaline water electrolysis system, and therefore can be used in a hydrogen production method that operates the alkaline water electrolysis apparatus at a pressure of 5 bar or higher, thereby enabling efficient hydrogen production.
[0203] Furthermore, as a method for producing hydrogen according to the present invention, the following method is preferably provided, which includes: adjusting the pressure control valve of the alkaline water electrolysis apparatus of the present invention to operate under a condition where the pressure on the hydrogen production side is 50 mbar or more greater than the pressure on the oxygen production side (operating under a pressure difference of 50 mbar or more obtained by subtracting the pressure on the oxygen production side from the pressure on the hydrogen production side). Thus, by operating under a pressure of 50 mbar or more applied from the hydrogen production side to the oxygen production side, the purity of the produced hydrogen can be improved.
[0204] The pressure difference obtained by subtracting the pressure from the hydrogen production side from the pressure on the oxygen production side is preferably 50 to 10,000 mbar, more preferably 50 to 8,000 mbar, and even more preferably 50 to 5,000 mbar.
[0205] The diaphragm included in the alkaline water electrolysis apparatus of the present invention can preferably be applied to a pressurized alkaline water electrolysis system. Therefore, it can be used in hydrogen production methods operating under conditions where a pressure of 5 bar or more is applied from the hydrogen production side to the oxygen production side of the alkaline water electrolysis apparatus, thereby enabling the efficient production of hydrogen with higher purity. In this case, the pressure difference obtained by subtracting the pressure from the oxygen production side from the pressure on the hydrogen production side is preferably 50 to 10000 mbar, more preferably 50 to 8000 mbar.
[0206] Example
[0207] The present invention will now be described in further detail with reference to embodiments, but should not be construed as limiting the scope of the invention. The water used is deionized water.
[0208] [Fabrication of diaphragms for hydrogen production]
[0209] <Example 1>
[0210] (1) Fabrication of the support
[0211] Using a calendering apparatus (super calender, manufactured by Mitsui Electric Precision Machine Co., Ltd., the same meaning applies hereinafter), PPS (polyphenylene sulfide) woven fabric (manufactured by NBC Meshtec, Inc., fiber diameter 56μm, opening ratio 60%) was calendered under conditions of a roll gap pressure of 90 kgf / cm, a roll temperature of 200℃, and a conveying speed of 20 m / min, resulting in a woven fabric support with a thickness of 70μm and a calendering ratio of 63%.
[0212] (2) Fabrication of diaphragms for hydrogen production
[0213] 8.5 g of polysulfone (trade name: Udel P-3500 LCD MB7, manufactured by Solvay, Mw: 80000) was added to 41.3 g of N-methylpyrrolidone (manufactured by Merck) and stirred at 60 °C for 5 hours until completely dissolved. Next, 2.4 g of PVP K30 (trade name, manufactured by Merck, polyvinylpyrrolidone) was added, and after stirring at 60 °C for 1 hour, 47.9 g of ZrO2 particles (trade name: High Purity Monoclinic Zirconias E101, manufactured by Luxfer MEL Technologies, median particle size (D50) approximately 0.8 μm) were added and stirred for 3 hours to obtain the casting solution.
[0214] Using a 250 μm thick coater, the obtained casting solution was cast onto a glass plate. The aforementioned woven fabric support was then placed on top, ensuring it was completely impregnated with the casting solution. Next, it was allowed to stand in a coagulation bath (pure water) cooled to 10°C for 5 minutes, forming a porous structure. The membrane was then further washed with water at 50°C for 10 minutes to peel it off from the glass plate. Finally, it was washed with water at 90°C for 1 hour to obtain the hydrogen production membrane of Example 1.
[0215] <Example 2>
[0216] In Example 1, a woven fabric support with a thickness of 50 μm and a calendering ratio of 71% was used as the woven fabric support. This support was obtained by calendering PPS woven fabric (manufactured by NBC Meshtec, fiber diameter 35 μm, opening ratio 60%) under the conditions of a roll gap pressure of 80 kgf / cm, roll temperature of 200°C, and conveying speed of 20 m / min. Otherwise, the hydrogen production diaphragm of Example 2 was produced in the same manner as in Example 1.
[0217] <Example 3>
[0218] In Example 1, a woven fabric support with a thickness of 80 μm and a calendering ratio of 67% was used as the woven fabric support. This support was obtained by calendering PPS woven fabric (manufactured by NBC Meshtec, fiber diameter 60 μm, opening ratio 60%) under the conditions of a roll gap pressure of 90 kgf / cm, roll temperature of 200°C, and conveying speed of 20 m / min. Otherwise, the hydrogen production diaphragm of Example 3 was produced in the same manner as in Example 1.
[0219] <Example 4>
[0220] In Example 1, a woven fabric support with a thickness of 210 μm and a calendering ratio of 70% was used as the woven fabric support. This support was obtained by calendering PPS woven fabric (manufactured by NBC Meshtec, fiber diameter 150 μm, opening ratio 60%) under the conditions of a roll gap pressure of 110 kgf / cm, roll temperature of 200°C, and conveying speed of 15 m / min. Otherwise, the hydrogen production diaphragm of Example 4 was produced in the same manner as in Example 1.
[0221] <Example 5>
[0222] In Example 1, a woven fabric support with a thickness of 100 μm and a calendering ratio of 67% was used as the woven fabric support. This support was obtained by calendering PEEK (polyetheretherketone) woven fabric (manufactured by SAFER Corporation, fiber diameter 75 μm, opening ratio 60%) under the conditions of a roll gap pressure of 100 kgf / cm, roll temperature of 200°C, and conveying speed of 10 m / min. Otherwise, the hydrogen production diaphragm of Example 5 was produced in the same manner as in Example 1.
[0223] <Example 6>
[0224] In Example 1, the organic polymer in the casting solution was changed from polysulfone to polyphenylsulfone (trade name: ULTRAZONE P, manufactured by BASF, Mw16000). Otherwise, the hydrogen production membrane of Example 6 was prepared in the same manner as in Example 1.
[0225] <Example 7>
[0226] In Example 1, a woven fabric support with a thickness of 120 μm and a calendering ratio of 67% was used as the woven fabric support. This support was obtained by calendering PP (polypropylene) woven fabric (manufactured by NBC Meshtec, fiber diameter 90 μm, opening ratio 60%) under the conditions of a calendering device with a roll gap pressure of 50 kgf / cm, a roll temperature of 140°C, and a conveying speed of 20 m / min. Otherwise, the hydrogen production diaphragm of Example 7 was produced in the same manner as in Example 1.
[0227] <Example 8>
[0228] In Example 1, the organic polymer in the casting solution was changed from polysulfone to polyethersulfone (trade name: SUMIKAEXCEL 5900P, manufactured by Sumitomo Chemical Company). Otherwise, the hydrogen production membrane of Example 8 was prepared in the same manner as in Example 1.
[0229] <Example 9>
[0230] In Example 1, the organic polymer in the casting solution was changed from polysulfone to polyvinylidene fluoride (trade name: SOLEF 6010, manufactured by Solvay). Otherwise, the hydrogen production membrane of Example 9 was prepared in the same manner as in Example 1.
[0231] <Comparative Example 1>
[0232] In Example 1, a woven fabric support with a thickness of 90 μm and a calendering ratio of 75% was used as the woven fabric support. This support was obtained by calendering PPS woven fabric (manufactured by NBC Meshtec, fiber diameter 60 μm, opening ratio 60%) under the conditions of a roll gap pressure of 70 kgf / cm, roll temperature of 170°C, and conveying speed of 20 m / min. Otherwise, the hydrogen production diaphragm of Comparative Example 1 was produced in the same manner as in Example 1.
[0233] <Comparative Example 2>
[0234] In Example 1, a woven fabric support with a thickness of 260 μm and a calendering ratio of 87% was used as the woven fabric support. This support was obtained by calendering PPS woven fabric (manufactured by NBC Meshtec, fiber diameter 150 μm, opening ratio 60%) under the conditions of a roll gap pressure of 90 kgf / cm, roll temperature of 180°C, and conveying speed of 20 m / min. Otherwise, the hydrogen production diaphragm of Comparative Example 2 was produced in the same manner as in Example 1.
[0235] <Comparative Example 3>
[0236] In Example 1, PPS woven fabric (manufactured by NBCMeshtec, fiber diameter 60 μm, thickness 110 μm, opening ratio 60%, calendering ratio 92%) was used directly as the woven fabric support without calendering. Otherwise, the hydrogen production diaphragm of Comparative Example 3 was made in the same manner as in Example 1.
[0237] The following measurements and evaluations were performed on various hydrogen production diaphragms.
[0238] The structure and results of each hydrogen production diaphragm are summarized in Table 1.
[0239] Dimensional stability during electrolytic cell assembly
[0240] The obtained hydrogen production diaphragm was immersed in pure water for 1 hour. It was then cut into circles with a diameter of 10 cm. For the obtained circular hydrogen production diaphragm, a tension of 150 N was applied for 5 minutes in the direction of the fiber axis of one of the orthogonal fibers and in the direction inclined at 45 degrees relative to the fiber axis, respectively, to prepare an observation sample.
[0241] The roundness was determined using the following method.
[0242] The obtained observation samples were placed on a flat platform so that they were fully contained within the frame when photographed. Image analysis was performed using ImageJ (developed by the National Institutes of Health) software, and the obtained roundness was used to evaluate the dimensional stability during the assembly of the electrolytic cell, according to the following criteria.
[0243] Additionally, roundness refers to the degree of roundness achieved by using 4πS / L, where the area of the sample being observed is S and its perimeter is L. 2 The calculated value is an indicator used to evaluate the degree of consistency with a perfect circle (roundness 1).
[0244] -Evaluation Criteria-
[0245] A: Roundness is 0.90 or higher.
[0246] B: Roundness is 0.87 or higher and less than 0.90.
[0247] C: Roundness is less than 0.87.
[0248] (Ion resistance)
[0249] The obtained hydrogen production diaphragm was immersed in a 30% potassium hydroxide aqueous solution (manufactured by Kanto Chemical Co., Inc.) at room temperature (25°C) overnight (20 hours), and then stamped into a circular shape with a diameter of 10 mm to prepare a sample for measurement.
[0250] In a two-chamber electrolytic cell with a nickel electrode at the current control terminal and a Luggin capillary filled with a 3M-KCl aqueous solution at the voltage control terminal, a 30% (w / w) potassium hydroxide aqueous solution was added as the electrolyte, and the temperature was maintained at 90°C. In constant current mode, the current density was 10 mA / cm². 2 The ion resistance was measured under the same conditions to obtain a blank value. Next, the sample prepared above was used as a diaphragm, and a 30% (w / w) potassium hydroxide aqueous solution was filled in the same way. The ion resistance was measured under the same conditions. The difference between the resistance value of the sample and the blank value was taken as the ion resistance value of the hydrogen production diaphragm.
[0251] Operation of the alkaline water electrolysis cell
[0252] The obtained hydrogen production diaphragm was immersed in pure water for 1 hour. It was then cut into a circular shape with a diameter of 10 cm. The resulting circular hydrogen production diaphragm was applied to a pressurized alkaline water electrolyzer. The results confirmed that the hydrogen production diaphragms prepared in Examples 1-9 did not protrude from the electrolyzer during assembly, enabling hydrogen production without electrolyte leakage or gas leakage due to defects. On the other hand, the hydrogen production diaphragms prepared in Comparative Examples 1-3 all protruded from the electrolyzer, resulting in electrolyte leakage and gas leakage due to defects.
[0253] In addition, the pressurized alkaline water electrolysis cell was constructed as follows, and its operation and evaluation were carried out.
[0254] The membrane was held between two sides using Ni foam (160 μm thick, 110 PPI porosity) manufactured by Goodfellow Corp. as electrodes, and then further held in place by two Ni bipolar plates with flow paths, secured with bolts. A 7.0 M potassium hydroxide (KOH) aqueous solution heated to 90 °C was supplied to the cathode and anode sides of each of the water electrolysis cells obtained above at a flow rate of 10 mL / min, while a flow rate of 0.1 A / cm... 2 After 4 hours of power-on, a water electrolysis cell was obtained after initial power-on.
[0255] Using the water electrolysis cell obtained after initial energization, at a temperature maintained at 90°C and a current of 0.8 A / cm 2Power was applied, and the pressure in the anode and cathode electrode chambers was adjusted to 30 bar using a pressure regulating valve for electrolytic cell evaluation. Note that adjusting the pressure to 30 bar means applying 30 bar to both the anode and cathode electrode chambers.
[0256] [Table 1]
[0257] <Notes on the table>
[0258] PPS: Polyphenylene sulfide
[0259] PEEK: Polyetheretherketone
[0260] PP: Polypropylene
[0261] PSf: Polysulfone
[0262] PPSf: Polyphenylsulfone
[0263] PES: Polyethersulfone
[0264] PVDF: Polyvinylidene fluoride
[0265] NMP: N-methylpyrrolidone
[0266] The fiber diameter d1 of the woven fabric support is used as the observation surface. The surface perpendicular to the thickness direction of the woven fabric support (i.e., the surface or back of the woven fabric support) is used as the observation surface. The arithmetic mean of the fiber diameters at 20 locations at the intersection of the warp and weft threads is calculated for the optical microscope image observed by transmitted light in a 1 mm square field of view.
[0267] The thickness d2 of the woven fabric support was calculated using a digital micrometer (manufactured by MESSMER BUCHEL) for a 10cm square woven fabric support. The arithmetic mean of the thicknesses at 20 points where the warp and weft threads intersect was calculated.
[0268] The thickness of the hydrogen production diaphragm is determined by obtaining a cross-sectional SEM (scanning electron microscope) image of the diaphragm at a magnification (e.g., 400x) that allows the diaphragm cross-section to be contained within a field of view. In the obtained cross-sectional SEM image, assuming no pores exist (assuming the pores are filled with organic polymers), the arithmetic mean of 20 measurements of the thickness are obtained by measuring the thickness at 20-point intervals.
[0269] The calendering ratios of the hydrogen production diaphragms in Comparative Examples 1 and 2 were 75% and 87%, respectively, which do not meet the requirements of this invention. Furthermore, the hydrogen production diaphragm in Comparative Example 3 was not calendered, therefore its calendering ratio was 92%, which also does not meet the requirements of this invention. These hydrogen production diaphragms from Comparative Examples 1 to 3 were deformed by applying tension after being cut into circular shapes, resulting in a roundness reduction to less than 0.87. When these hydrogen production diaphragms from Comparative Examples 1 to 3 were used in a pressurized alkaline water electrolyzer, electrolyte leakage and current leakage occurred during operation.
[0270] In contrast, the calendering ratios of the hydrogen production diaphragms in Examples 1-9 are all below 73%, resulting in minimal deformation after being cut into circular shapes and subjected to tension. Their roundness is maintained at 0.87 or higher, demonstrating excellent dimensional stability when assembling electrolyzers. Furthermore, when these hydrogen production diaphragms from Examples 1-9 are applied to pressurized alkaline water electrolyzers, electrolyte leakage and current leakage are suppressed during operation, thereby enabling hydrogen production. Moreover, the ion resistance of these hydrogen production diaphragms from Examples 1-9 is 0.03-0.08 Ω·cm. 2 The ion resistance of the hydrogen production diaphragms in Comparative Examples 1-3 was 0.08 or 0.13 Ω·cm. 2 The ionic conductivity is improved to the same or lower level. It is believed that when a woven fabric support with a calendering ratio of 73% or less undergoes calendering, the fiber intersections fuse together, resulting in a decrease in the open area ratio and a decrease in ionic conductivity. Therefore, compared to a woven fabric support with a calendering ratio exceeding 73%, the hydrogen production diaphragm of the present invention exhibits ionic conductivity at the same or higher level, in addition to excellent dimensional stability.
[0271] In the case where the woven fabric support material is at least one of polyphenylene sulfide (PPS) and polyether ether ketone (PEEK), the dimensional stability and ionic conductivity during electrolytic cell assembly are superior (compared to Examples 3 and 5 of Example 7). Furthermore, in the case where the organic polymer is at least one of polysulfone (PSf), polyphenylene sulfone (PPSf), and polyether sulfone (PES), the dimensional stability during electrolytic cell assembly is superior (compared to Examples 1, 6, and 8 of Example 9).
[0272] This application claims priority based on Japanese Patent Application 2024-055617, filed on March 29, 2024, the contents of which are incorporated herein by reference as part of the description herein.
[0273] Symbol Explanation
[0274] 10-Alkaline water electrolysis system; 11-Diaphragm for hydrogen production; 12-Cathode electrode; 13-Anode electrode; 14-High-concentration alkaline aqueous solution; 20-Alkaline water electrolysis system; 30-Alkaline water electrolysis system; 31-Diaphragm for hydrogen production; 32-Cathode catalyst layer; 33-Anode catalyst layer; 34-Gas diffusion layer; 35-Bipolar plate; O2-Bubbly oxygen; H2-Bubbly hydrogen; OH- - - Hydroxide ion, e - - Electron, d2 - thickness of the intersection, F1 - latitude, F2 - longitude.
Claims
1. A membrane for hydrogen production, comprising a woven fabric support and a porous material containing an organic polymer, wherein, The calendering ratio of the woven fabric support, calculated using the following formula, is 73% or less. Rolling ratio = {d2 / (2×d1)}×100% In the above formula, d1 represents the fiber diameter of the woven fabric support, and d2 represents the thickness of the woven fabric support.
2. The diaphragm for hydrogen production according to claim 1, wherein, The fiber diameter d1 of the woven fabric support is less than 180 μm.
3. The diaphragm for hydrogen production according to claim 1, wherein, The thickness d2 of the woven fabric support is less than 250 μm.
4. The diaphragm for hydrogen production according to claim 1, wherein, The material of the woven fabric support includes at least one of polyphenylene sulfide and polyetheretherketone.
5. The diaphragm for hydrogen production according to claim 1, wherein, The organic polymer comprises at least one of polysulfone, polyethersulfone, and polyphenylsulfone.
6. An alkaline water electrolysis component comprising the diaphragm for hydrogen production as described in claim 1.
7. An alkaline water electrolyzer comprising a diaphragm for hydrogen production as described in any one of claims 1 to 5 or an alkaline water electrolyzer component as described in claim 6.
8. An alkaline water electrolysis device comprising the alkaline water electrolysis cell of claim 7.
9. A method for producing hydrogen, comprising: The alkaline water electrolysis device according to claim 8 is operated under a pressure of 5 bar or higher.
10. A method for producing hydrogen, comprising: The alkaline water electrolysis apparatus of claim 8 is operated under conditions where a pressure of 50 mbar or more is applied from the hydrogen production side to the oxygen production side.
11. A method for manufacturing a hydrogen production membrane, wherein the hydrogen production membrane is the hydrogen production membrane according to any one of claims 1 to 5, and the method for manufacturing the hydrogen production membrane comprises: A porous material containing an organic polymer is formed by wet phase separation with a woven fabric support disposed in a coating film. The coating film is formed from a casting solution in which the organic polymer is dissolved. The woven fabric support is a woven fabric support that has undergone calendering and has a calendering ratio of 73% or less as calculated by the following formula. Rolling ratio = {d2 / (2×d1)}×100% In the above formula, d1 represents the fiber diameter of the woven fabric support, and d2 represents the thickness of the woven fabric support.
Citation Information
Patent Citations
Alkaline water electrolysis separator
JP2023531792A
Object moving device
JP2024055617A